Role activity diagram-based discrete event simulation model for healthcare service delivery processes. Issue 1 (2nd January 2017) - Shukla, Nagesh; Keast, John E.; Ceglarek, Darek
ABSTRACT: In case of health care systems, discrete event simulations (DESs) are useful techniques to identify problematic process issues. However, currently available simulation models often use a simplified flow chart as an input which represents patient flow obtained from on-site observations and interviews complemented with historic patient data. This is insufficient in modelling important interactions between clinical staff, equipment and patients, causing the resultant models to be incomplete and unrealistic. This in turn leads to oversimplified outputs from any simulations. This paper presents a systematic methodology for the development of DES model from process mapping model based on the role activity diagram (RAD) notations. RAD allows complex collaborative health care service delivery processes to be modelled as roles, interactions, actions and decision questions. The workflow simulation modelling methodology based on RADs includes: (1) development of RAD model of the service delivery process; (2) data model for RAD-based service delivery process; (3) developing DES model based on RAD; and (4) adding dynamic attributes and validating DES model. The methodology is demonstrated through a case study of magnetic resonance (MR) scanning process of radiology department in a large hospital.